Influence of walnut on hepatic ischemia-reperfusion injury in streptozotocin-induced diabetic rats - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2021)
Nutritional benefits of walnut are well known; however, currently, there is no research showing that walnut can be used as an antioxidant in people with diabetes mellitus (DM). Therefore, the objective of this study was to investigate the protective effects of walnut against oxidative stress in hepatic ischemia-reperfusion (I/R) injury in sheptozotocin (STZ) induced diabetic rats. Animals were divided into four-groups (Control, DM, DM+I/R, DM+I/R+Walmit; n=6 each). STZ treatment and I/R procedures were not performed in the control group, other groups were first administered 60-mg/kg STZ intraperitoneally. After 48-h, animals were considered as DM. After four-weeks, DM groups were subjected to 30 min of hepatic-ischemia followed by 45-min reperfusion. DM+I/R+Walnut group was fed pellet-feed mixed with walnut (2 g/100 g/day) until I/R. Other groups were fed only with pellet-feed. At the experimental end, animals decapacitated, blood samples collected to determine senim levels of tumor necrosis factor (TNF)-alpha, interleukin (IL)-6, malondialdehyde (MDA). Liver samples were collected for histological examinations. Forty-eight-hours after STZ, animals showed significant weight-loss compared to age-matched controls, blood glucose levels were increased (P< 0.05). Four-weeks post- STZ, blood glucose also increased significantly. TNF-alpha, MDA substantially increased in the DM+/I/R group (P< 0.01), whereas in DM+I/R+Walnut group this increase was lesser (P< 0.05). Aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase (LDH) levels were lower in DM+/I/R+Walnut vs. DM+I/R groups; but higher than DM/control groups (P< 0.05). Positive-correlation observed between TNF-alpha and IL-6 (Spearman r:0.793; 1) ,
Keywords: Antioxidant; Diabetes mellitus; Histopathology; Inflammatory response; Ischemia-rewfusion injury; Rat; Walnut; OXIDATIVE STRESS; FREE-RADICALS; FATTY-ACIDS; RESVERATROL; ANTIOXIDANTS; KIDNEY; CELLS